Clínicas jurídicas: por um novo modelo de ensino do direito no Brasil - Fortes, Diego Monteiro de Arruda (2018)
This dissertation starts with a brief report of the historical aspects of the creation of the Brazilian Law course, informing that throughout the years there has been only changes in the curricular matrices of the legal education that was not able to promote an alternative to the current teaching based on lectures. As an exit to this scenario, the study proposes to research the participatory methods idealized initially in the United States of America, that later, arrived in Latin America, and then, came to Brazil, based on an active student posture. Then by bibliographical review a direct observation is made of the functioning of the Legal Clinics in four different Law faculties in São Paulo capital, showing the importance of the clinical method in the current Brazilian Legal education, given that, it contributes to the development and improvement of the technical and scientific career of the student. The student works with real cases. It is an effective pedagogical tool, especially in the training of the law interpreters, it is an unparalleled experience of teaching and learning, with positive aspects for lectures, students and the society as a whole.